FORMULASI GEL MINYAK KAYU MANIS (Oleum Cinnamomi) SEBAGAI PEMBERSIH TANGAN MENGGUNAKAN VARIASI KONSENTRASI CARBOPOL - Faradiba Faradiba; Ermina Pakki; Fanny Fardiyani (As-Syifaa Jurnal Farmasi, 2009)
As investigation has been done on cinnamomi oil gel formulation as hand clean use carbopol gel bases. The aim of the investigation was to select the most stable formula if cinnamomi oil through stability evaluation which done by organoleptic observation, viscosity and yield value determination. It was made three formula with several different concentration carbopol in this investigation that are 0,3 %, 0,4 % and     0,5 %. Of the  result organoleptic observation there was no alternation before and after stress condition. Result statistic analyse on viscosity data shown that there was an influence of gel formula to viscosity before and after stress condition. At formula I and III shown that there was a  very real influence between of  before and after stress condition, while at formula II shown that there was no real influence. Result statistic analyse on yield value data shown that there was an influence of gel formula to yield value before and after stress condition. At formula I shown that there was a  real influence between of  before and after stress condition, at formula III shown that there was a  very real influence between of  before and after stress condition, while at formula II shown that there was no real influence. The conclution was formula II have the most optimal stability  use concentration of carbopol 0,4 %.Key Words : Oleum Cinnamomi, Hand Clean, Carbopol